Land And District Office of Sepang, Bangunan Tun Aziz, Bandar Baru Salak Tinggi 43900 Sepang / Nurul Syamimi Omar Zaman - Omar Zaman, Nurul Syamimi (University Technology MARA Sarawak, 2016)
Sepang District and Land Office located in Bangunan Tun Aziz, Bandar Baru Salak Tinggi, 43900 Sepang, Selangor Darul Ehsan. Sepang District and Land Office is under the State Government. It vision is leading best administration towards developed of Sepang prosperous and welfare. It mission is catalyse organization through quality service and friendly to achieve holistic development. They are several objectives of the company. The objectives are strengthening the ability and organization capacity to improve the efficiency of service delivery system, strengthening organization governance and culture values towards excellence organization, strengthening land management and administrative for the prosperity of the state, increasing the number of public facilities and infrastructure to improve citizen life quality, revitalizing urban and rural development and also strengthening the socioeconomic in a holistic way for the prosperity of the citizen and improve public safety to maintain the unity of city.